PENERAPAN PENDIDIKAN KARAKTER SISWA KELAS V SD MUHAMMADIYAH BLORA MELALUI PROFIL PELAJAR PANCASILA - Kusuma Wardhani, Dian; Utami, Yeri (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2023)
The purpose of this study was to find out the application of character education for third grade students through a program to strengthen the profile of Pancasila students in elementary schools, and the benefit of this research was for readers to know how to apply character education to third grade students through a program to strengthen the profile of Pancasila students. The approach used in this research is a descriptive qualitative approach. Data collection techniques carried out by researchers in the form of interviews, observations, and questionnaires. Data analysis techniques used in this study are data reduction, data presentation and conclude the data that has been obtained by researchers from observations. Based on the results of the researcher's interview with the third grade teacher at SD Muhammadiyah Blora, the answer to the researcher's question was that the third grade teacher had implemented character education in accordance with strengthening the profile of Pancasila students through the components of Pancasila student attitudes that were explained in the previous paragraph. The third grade teacher explained that there were almost 85% of students who had instilled the character of students according to the profile of Pancasila students, and 15% of students still did not have the character as students of the Pancasila profile. Character education through the Pancasila profile strengthening program is basically an activity to encourage the birth of good human beings, who have six main characteristics, namely, critical reasoning, creative, independent, faithful, devoted to God Almighty, noble character, mutual cooperation and global diversity. It is hoped that the implementation of character education through the program to strengthen the profile of Pancasila students is able to make students become better human beings and able to realize the values of character and noble character that can be realized in everyday life.Keywords: Independent Attitude, Strengthening the Profile of Pancasila Students, Elementary Schools